On the virtues and vices of combining theories: The case of institutional and actor-network theories in accounting research - Modell Sven; Vinnari Eija; Lukka Kari (PERGAMON-ELSEVIER SCIENCE LTD, 2022)
This paper examines the possibilities and challenges of combining method theories in accounting research through an analysis of studies which combine insights from institutional theory (IT) and actor network theory (ANT). We investigate the paradigmatic challenges associated with combining these method theories and whether and how scholars have dealt with such challenges. We demonstrate how the combination of these method theories in a single study gives rise to considerable paradigmatic tensions. The most significant tensions relate to the two method theories' diverging ontological conceptions of the nature of social structures and agency and their very different epistemological views of the role of theory. Moreover, our review of extant accounting research combining IT and ANT indicates that a large number of studies simply ignore such tensions and do not provide deeper reflections on the paradigmatic implications of combining these method theories. Whilst recognizing the substantive contributions emerging from this body of research, we question whether continued rapprochement between IT and ANT is the most appropriate way forward and suggest alternative theoretical paths for examining the institutionalization of accounting. We also call on accounting researchers to exercise much greater reflexivity regarding the paradigmatic implications of combining method theories as well as the more general justifiability of such practices as a vehicle for advancing our understanding of accounting as a social and organizational practice. (C) 2017 Elsevier Ltd. All rights reserved.